UJI AKTIVITAS EKSTRAK ETANOL DAUN ALPUKAT (Persea americana Mill.) TERHADAP PENYEMBUHAN LUKA BAKAR PADA PUNGGUNG MENCIT PUTIH JANTAN (Mus musculus) - Triswanto Sentat; Rizki Permatasari (Jurnal Ilmiah Manuntung, 2015)
Activity Assay of avocado leaf (Persea americana Mill.) ethanol extract on burn healing at back skin of white male mice (Mus musculus) aims to determine the best concentration of avocado leaf ethanol extract to healing burn on back skin of mice. Extract of avocado leaf obtained by maceration method using ethanol 70%. Burn made by soldering iron modified with square plate (size 1 x 1 cm2), during 2 seconds contact at the skin and make the skin formed blister. Observation of the burn area was doing daily for 14 days, and also the treatment with the 3 concentrations extract variation (20%,35%, and 50%), negative control and positive control. Result of research show that all avocado leaf ethanol extract in concentrations 20%, 35% and 50% have good activity in burn healing, from first day until 14th day they showed percentage of burn recovering successively equal to 86%, 88% and 90%. Negative control showed that process healing of burn was very tardy, only has percentage of burn recovering equal to 32,67% on 14th day, while positive control showed 100% burn healing on 11st day. The best concentration of  avocado leaf ethanol extract on healing burn is 50% with 90% burn healing